Bimbingan Teknis Guru dan Kepala Sekolah Dalam Menyusun Modul Ajar Pada Kurikulum Merdeka - Agus Mulyanto; Okke Rosmala Dewi; Asep Deni Normansyah; Fidya Arie Pratama; Agus Nurkholiq; Ismail Hasim; Mujiyatna; Maesaroh; Sri Tubillah Noor; Siti Honiah Mujiati; Masyudi; Rhani Sri Ervina; Prihatining Tyas (Madani : Indonesian Journal of Civil Society, 2023)
This Community Service Activity was held because the competency demands required by teachers in the independent curriculum were getting higher. Therefore Technical Guidance was expected to be one of the solutions for every teacher and school. Because in this Technical Guidance, all information is presented operationally and technically, with competent sources, a short duration, and is not boring. So, Participants can take part in activities to improve their competence quickly. The research that underlies the preparation of this Community Service article is qualitative research with a descriptive method, where the descriptive study is research conducted to describe or describe the implementation of the Webinar and Bimtek, which includes themes, timeliness, atmosphere, the competence of resource persons, completeness of the material, service/attitude of the committee, and tools. Furthermore, the success of this Community Service activity can be measured starting from preparation, participation, implementation, and evaluation. This Community Service activity resulted in several products, including a 32 (thirty-two) hour certificate, from the Chancellor of the Nusantara Islamic University at Bandung, the Chancellor of the "45" Islamic University at Bekasi, and the BAZNAS at Bekasi City. In addition, Participants also received Technical Guidance material and assignment templates in preparing teaching materials for the Strengthening Pancasila Student Profile Project. This Community Service activity also resulted in several institutional collaborations as a form of academic concern